Lightning accidents in Uganda - Mary, Ahurra Kulyaka; Gomes, Chandima

(untitled)
This paper addresses the lightning safety environment in Uganda that requires urgent and serious attention of the international expert community. We present recent statistics of reported lightning incidents in Uganda which show that the number of injuries and deaths are overwhelmingly high during year 2011 thus the situation can be declared critical. During the five-year period from January 2007 to December 2011, there were 91 reported lightning accidents which accounted for a total number of 150 deaths and 584 cases of personal injuries to which the victims did not succumb. Out of 150 deaths 95 reported in 2011. The actual number in each case may be much higher as many deaths and injuries go unnoticed due to lack of communication between rural communities and government authorities or media sources. The detailed analysis of several incidents reveals that injuries and deaths are basically due to both lack of awareness and absence of proper protection and safety schemes. The decisive factors of the ill-effects of incidents are time of the day, month of the year, part of the country, location of the incident etc. Most of the accidents have occurred either in the afternoon or in the evening. A spread of incidents can be seen throughout the six month period from June to November with June as the month of highest reported deaths. The highest number of incidents has been reported in the Northern Province of the country. Interestingly, the highest number of incidents, deaths and injuries has occurred while the victims were inside permanent structures. After analyzing these incidents a stepwise procedure is proposed to curb such incidents in the future.